A formação inicial de professores de química e o exercício da docência na escola: que discursos estão em jogo? - Christino, Verônica Caldeira Leite (2013)
This research deals with the discourses surrounding teaching and the teaching profession at the university and at school in order to analyze how the trainees and beginning teachers of chemistry deal with different concerns that "being a teacher" brings and what effects these different discourses would have on the practice of teaching as well as think about monitoring the practices of trainees of Chemistry at the school where I work. Research subjects were students graduating in the period 2011/2, beginner teachers of Chemistry and trainees in the Colégio Municipal Pelotense in the period 2011/2 to 2012/1, all students or graduates of the Degree Course in Chemistry UFPel. The survey was conducted with a methodology that meets assumptions of discourse analysis, based on the theory of Michel Foucault (2012), considering speech as a practice that produces the objects about which it speaks. Interviews, questionnaires and records of responses to a hypothetical situation created for the interviewees to manifest their opinion about the undergraduate program and being a teacher were taken as analysis corpus. Data analysis showed the recurrence of an utterance that permeates different discourses, in the university and in the school, in which being an elementary school teacher is something diminished, and it is possible to see, throughout the study, its effects on the formation of professional identity . From the results of the analysis, it is clear that there is an estrangement of the school by subjects who begin teaching, either as a trainee or as a beginner teacher. I see the proposition of thinking actions for monitoring beginner teachers and especially trainees as a way to draw attention to the role of the university and the school as teacher training agencies, from the initial formation, which may contribute to soften estrangements between university and school, pointed by the subjects of this research.